THE EFFECT OF SERVICE QUALITY AND PRICE ON USER LOYALTY CONTRACTOR SERVICES PT. HADI JAYA BORE LAND SURABAYA - R. Abdul Haris, Inayatusshobah, Agustina Pujiastutik (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The research conduct to determine the simultaneous, partial, and dominant influence between service quality and price variables on contractor service users’ loyalty at PT. Hadi Jaya Bore Land Surabaya. This type of research is quantitative. The population in this study are contractor service users at PT. Hadi Jaya Bore Land Surabaya. Took a total of 50 service users and 45 respondents taken randomly. The method of data analysis in this study uses a validity test, a reliability test, a classic assumption test, multiple regression analysis, a hypothesis test, and a coefficient of determination. The results showed that the quality and price of service simultaneously or partially influenced customer loyalty, and the most influential (dominant) variable on customer loyalty was service quality.